TAMI-73. GLIOBLASTOMA CELL POPULATIONS WITH DISTINCT ONCOGENIC PROGRAMS RELEASE PODOPLANIN AS PROCOAGULANT EXTRACELLULAR VESICLES. (12th November 2021) - Tawil, Nadim; Bassawon, Rayhaan; Meehan, Brian; Montermini, Laura; Nehme, Ali; Choi, Dongsic; Spinelli, Cristiana; Adnani, Lata; Mohammadnia, Abdulshakour; Couturier, Charles; Petrecca, Kevin; Rak, Janusz
Abstract: BACKGROUND: Vascular anomalies, including thrombosis, are a hallmark of glioblastoma (GBM) and an aftermath of dysregulated cancer cell genome and epigenome. Up-regulation of podoplanin (PDPN) by cancer cells has recently been linked to an increased risk of venous thromboembolism in glioblastoma patients. Thus, regulation of this platelet activating protein by transforming events and release from cancer cells is of considerable interest. AIMS: I. Investigate the pattern of PDPN expression and characterize PDPN-expressing cellular populations in GBM. II. Evaluate the contribution of oncogenic drivers to PDPN expression in GBM models. III. Investigate the potential involvement of extracellular vesicles (EVs) as a mechanism for systemic dissemination of PDPN and tissue factor (TF). IV. Examine the role of PDPN in intratumoral and systemic thrombosis. METHODS: Bioinformatics (single-cell and bulk transcriptome data mining), GBM cell lines and stem cell lines, xenograft models in mice, ELISA assays for PDPN and TF, platelet (PF4) and clotting activation markers (D-dimer), EV electron microscopy, density gradient fractionation, and nano-flow cytometry. RESULTS: PDPN is expressed by distinct glioblastoma cell subpopulations (mesenchymal) and downregulated by oncogenic mutations of EGFR and IDH1 genes, via changes in chromatin modifications (EZH2) and DNA methylation, respectively. GBM cells exteriorize PDPN and/or TF as cargo of exosome-like EVs shed both in vitro and in vivo. Injection of glioma PDPN-EVs activates platelets. Increase of platelet activation (PF4) or coagulation markers (D-dimer) occurs in mice harboring the corresponding glioma xenografts expressing PDPN or TF, respectively. Co-expression of PDPN and TF by GBM cells cooperatively increases tumor microthrombosis. CONCLUSION: Distinct cellular subsets drive multiple facets of GBM-associated thrombosis and may represent targets for diagnosis and intervention. We suggest that the preponderance of PDPN expression as a risk factor in glioblastoma and the involvement of platelets may merit investigating anti-platelets for potential inclusion in thrombosis management in GBM.